Analysis of inflammatory cells in osseointegration of CpTi implant radiated by low level laser therapy - Eman I Al- Tamemi (College of Dentistry/ University of Baghdad, 2015)
Background: Dental implants provide a unique treatment modality for the replacement of a lost dentition .This is accomplished by the insertion of relatively an inert material (a biomaterial) into the soft and hard tissue of the jaws, there by providing support and retention for dental prostheses. Low level laser therapy (LLLT) is an effective tool used to prompt bone repair and remodeling, this has referred to the biostimulation effect of LLLT. The Aim of this study was to evaluate the effects of inflammatory cells on osseointegration of CpTi implant irradiated by low level laser. Materials and Methods: thirty two adult New Zealand white rabbits, received titanium implants were inserted in the tibia. The right side is considered as experimental groups and the left side considered as control groups. Low power diode laser (GaAlAs ) with wave length (904nm) and (5mW)power applicated with the right implants . The sample divided into four groups, eight rabbits were sacrificed at four interval 4days, 1 weeks, 2weeks, and 6weeks respectively. Histological and inflammatory analyses were done for each interval. Results: Histological examination showed acceleration of bone formation and more rapid healing process in the screw implant with laser irradiation than in the control implant .inflammatory analysis showed dramatic decrease with the presence of laser irradiation especially with advancing time. Conclusion: This study illustrated that the inflammatory cells were reduced in osseointegration of dental implant treated with LLLT. Key words: Dental Implants, low level laser therapy, inflammatory cell.